E-Learning Management Of English 1 (Reading And Writing) At LTC Muhammadiyah University Of Yogyakarta - RUSLI, Tri Indah; , Prof. Endang Fauziati, M.Hum; , Dr. Agus Ulinuha, M.T (2013)
The objectives of this study are to describe management the E-Learning of English 1 at LTC Muhammadiyah University of Yogyakarta. Specifically, this research reveal briefly: First, The components covered in planning of the ELearning that covered syllabus, and learning objectives. Second, The organization of the E-Learning that covered method of teaching, instruction material, teacher and student's role. Third, models of evaluation. This is a qualitative research with micro ethnography approach. This research is conducted at LTC Muhammadiyah University of Yogyakarta. The informants of the research are Head of Language Training Centre, lecturers, and students. The techniques of data collection are through deep interview, observation, and documentation. The techniques of data analysis are by reducing the data, displaying the data, and then drawing conclusions by using QDA Miner Lite soft-program. The data validation is conducted through triangulation of the data. The results of the research show that the planning of English 1 starts from the arrangement of syllabus by the team as well as establish the learning objectives. However, the lecturer does not provide the E-Learning activity in lesson plan likewise the E-Learning does not put into curriculum as the component of planning, that makes the planning of E-Learning of English 1 is not perfect yet. The organization of the E-Learning of English I is used asynchronous method The material used are printer, unprinted and merge material that ready in the LTC official website . The lecturer's roles are as facilitator, mentor, motivator and evaluator. Student's roles are as performer and evaluator. Evaluation conducted is formative evaluation such as home assignment, and Quiz. Summative evaluation consists of mid-term and final examination, this evaluation conducted through face-to face meeting not in E-Learning.